2000
DOI: 10.1128/mcb.20.8.2760-2773.2000
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Regulation of Ornithine Decarboxylase Synthesis in Neurospora crassa

Abstract: Ornithine decarboxylase (ODC) of the fungus Neurospora crassa, encoded by the spe-1 gene, catalyzes an initial and rate-limiting step in polyamine biosynthesis and is highly regulated by polyamines. In N. crassa, polyamines repress the synthesis and increase the degradation of ODC protein. Changes in the rate of ODC synthesis correlate with similar changes in the abundance of spe-1 mRNA. We identify two sequence elements, one in each of the 5 and 3 regions of the spe-1 gene of N. crassa, required for this poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The translation of these newly unmasked transcripts explains the rapid and dramatic rise in detectable levels of spermidine that precedes later maturation phases of the spermatids (Figure 1). In other organisms, polyamines have been implicated in the regulation of their own biosynthesis pathways (Hoyt et al, 2000). The large rise in spermidine concentration late in development can be blocked by the addition of CHA at a point when the spermatids are already present, thereby showing that the enzyme is responsible for the synthesis of the polyamine.…”
Section: A Rise In Spermidine Concentration In Spermatogenous Cells Imentioning
confidence: 97%
“…The translation of these newly unmasked transcripts explains the rapid and dramatic rise in detectable levels of spermidine that precedes later maturation phases of the spermatids (Figure 1). In other organisms, polyamines have been implicated in the regulation of their own biosynthesis pathways (Hoyt et al, 2000). The large rise in spermidine concentration late in development can be blocked by the addition of CHA at a point when the spermatids are already present, thereby showing that the enzyme is responsible for the synthesis of the polyamine.…”
Section: A Rise In Spermidine Concentration In Spermatogenous Cells Imentioning
confidence: 97%
“…Studies on the 5Ј leader of ODC mRNA in Neurospora crassa (36), showed that a region that we now recognize contains the uCC in Pezizomycotina (Fig. 1Bvi), causes close to 30-fold repression of expression of ODC protein.…”
Section: Discussionmentioning
confidence: 99%
“…Only wt cells labeled with 4TU gave a strong signal over background ( Figure S3, A and B). As expected, new transcription was necessary to obtain 4TU-labeled RNA: preincubation with the general transcription inhibitor thiolutin, which has been shown to decrease transcription in N. crassa (Hoyt et al 2000;Lee et al 2009), severely reduced 4TU incorporation, as did chilling cells on ice ( Figure S3, C and D). Incorporation of 4TU into RNA rapidly diminished when excess uracil was added to cultures ( Figure S3E) and 4TU itself had minimal impact on N. crassa growth under the experimental conditions used (,30 min incubation) or during growth for extended periods ( Figure S3F), similar to its minimal effects on growth in S. cerevisiae (Munchel et al 2011) and S. pombe (Sun et al 2012).…”
Section: N Crassa Nmd Mutations Increase the Levels And Stability Ofmentioning
confidence: 99%